The Clinical Trials Transformation Initiative (CTTI) - Alberto Grignolo (Istituto Superiore di Sanità, 2011)
The Clinical Trials Transformation Initiative (CTTI) is a public-private partnership created in 2007 between the United States Food and Drug Administration (FDA) and Duke University for the purpose of identifying practices that will increase the quality and efficiency of clinical trials. The initiative was generated from the realization that the clinical trials system in the United States has been suffering as a result of increasingly longer study start-up times, slowing enrollment of patients into trials, increasing clinical trial costs, and declining investigator interest in participating in clinical trials. Although CTTI was created to address a crisis for US clinical research, it seeks to identify practice improvements that can be applied internationally, and is therefore engaging international collaborators with international efforts that have similar objectives. CTTI's approach is to involve all sectors in the selection, conduct, and interpretation of its projects; to keep the dialogue open across sectors; to provide evidence that can influence regulatory guidance, and to attempt to create a "level playing field" when recommending change. The hope is that a broad and diverse data-driven discussion of the important issues in clinical trials will lead to meaningful change for the benefit of all concerned, and importantly for patients.